Analisis Faktor Penghambat Promosi Produk UMKM Gerabah di Desa Wisata Banyumulek, Lombok Barat - Samsul Hakim (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
This research focuses on identifying the inhibiting factors in promoting ceramic SME products in Banyumulek Tourist Village and formulating strategies for product promotion. The objectives are to analyze the inhibiting factors and devise promotion strategies. Qualitative descriptive and SWOT analysis methods were employed, with data collected through observation, interviews, and documentation. Purposive sampling was used to select informants. The findings suggest the utilization of Weakness-Opportunities (WO) strategies, leveraging weaknesses to exploit existing opportunities. Recommendations include maximizing promotion to reach wider audiences, enhancing the knowledge of SMEs through promotional media, and business development with government support